2019
DOI: 10.13005/bpj/1617
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancers and the Roles of Natural Compounds as Potential Chemotherapeutic and Chemopreventive Agents

Abstract: Among all types of human cancers, lung cancer is one of the most common and has the highest mortality rate. Two major groups of lung cancer based on histological features are non-small cell lung cancers (NSCLCs) and small cell lung cancers (SCLCs). NSCLCs are further subdivided into few subtypes such as adenocarcinoma (AD), squamous cell carcinoma (SCC) and large cell carcinoma(LCC). Focusing on specific treatments or molecular targeted therapy for each type of lung cancers promising the better results as each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Small Cell Lung Carcinoma (SCLC) SCLC is a destructive type of cancer with increasing patient mortality risk. Over the past few decades, no appropriate treatment has been found effective against SCLC [41,77]. The survival and resistance of SCLC cells are mainly attributed to the overexpression of anti-apoptotic BCL-2 family members, such as BCL-XL and MCL-1.…”
Section: Pancreatic Ductal Adenocarcinoma (Pdac)mentioning
confidence: 99%
“…Small Cell Lung Carcinoma (SCLC) SCLC is a destructive type of cancer with increasing patient mortality risk. Over the past few decades, no appropriate treatment has been found effective against SCLC [41,77]. The survival and resistance of SCLC cells are mainly attributed to the overexpression of anti-apoptotic BCL-2 family members, such as BCL-XL and MCL-1.…”
Section: Pancreatic Ductal Adenocarcinoma (Pdac)mentioning
confidence: 99%
“…The SCC subtype is one of the primary malignancies of lung cancer, and it is characterized by late diagnosis and poor survival rate [ 33 , 34 , 35 ]. Thus, evaluating the underlying molecular mechanisms of lung SCC is crucial to understand the disease etiology.…”
Section: Discussionmentioning
confidence: 99%
“…β-escin (a RhoA/ROCK inhibitor) for instance, has been evaluated to not cause significant body weight loss or histologic cytotoxicity on normal mice after 34 weeks of treatment, which indicates that this natural compound is unable to jeopardize general health (108). As reviewed by Surien et al (110), a number of natural compounds have been proven to be beneficial in the treatment of lung cancer at pre-clinical studies. From the literature search, the present review identified 6 different studies that evaluated ROCK expression following treatment with natural compounds (46,80,102,106-108).…”
Section: Rock Signaling Pathway Inhibition In Lung Cancermentioning
confidence: 99%